Student engagement as a mediator between online classroom management and learning outcomes in Beijing universities - Fei, Li Yi; Radzi, Norfariza Mohd; Hoque, Kazi Enamul (Institute of Advanced Engineering and Science, 2025)
Online classroom management is considered essential for promoting student learning outcomes and engagement. This study examines the relationship between online classroom management and student learning outcomes, with student engagement as a mediator. A cross-sectional survey method was employed to collect data via questionnaires distributed through Google Forms. Respondents were selected using multi-stage cluster sampling from six universities in Beijing, China. A total of 400 valid questionnaires were analyzed quantitatively using SPSS to address the research questions. The findings indicate that online classroom management positively correlates with student engagement and learning outcomes. Moreover, student engagement significantly mediates the relationship between online classroom management and student learning outcomes. The study validates the model that online classroom management, mediated by student engagement, positively influences university students’ learning outcomes, thus supporting the research hypotheses based on the relationships among the variables. This study contributes to the integration of theory and enhances the understanding of the relationship between online classroom management and student learning outcomes. Additionally, it offers insights for policymakers and practitioners on how to support online classroom management and improve student learning outcomes.